Super-resolution applications using cylindrical vector optical beams - Yuan, Xiaocong. (2009)
Cylindrical vector beams (CYB) are solutions of Maxwell's equations that exhibit axially symmetric polarizations over their cross sections. When focused with a high numerical aperture lens, CYB polarized in the radial direction produces a longitudinal on-axis electric field at the focus plane. This therefore provides a means of resolution enhancement (a focal spot size significantly smaller than the diffraction limit) and better focusing qualities compared to conventional linear or circular polarizations. This project provides the foundation stage in a larger strategic goal aimed at the implementation of such beams for practical engineering and applied scientific research. Work in this project was carried out towards the conceptualization, fabrication and the experimental testing of a compact technique for generating CYBs. It was noted that the current state of the science predominantly involves the conversion of monochromatic continuous wave (cw) lasers into CYBs. Hence part of our efforts was also directed towards investigating the potential of generating CYBs in the qasi-monochromatic pulsed regime by directly converting the output of femtosecond pulsed lasers. Through vector diffraction modelling, we study the polarization dependent focus profiles and find that when radial polarization is used as the illumination source in multiphoton experiments, the focus spot has an envelope that is comparable to the single-photon profile.